(untitled) (Andamios, Revista de Investigación Social, 2012)
In this article I propose to examine the relationship between citizenship and social rights, which some authors call social citizenship. I review some objections that are made to social rights, discuss and put in question the fact do depend on the social rights of citizenship status and assume that they should be granted to any person regardless of whether a citizen or not.